Female unemployment and economic growth in Cameroon: An estimation of a nonlinear Okun's law specification by the ARDL cointegration model - Jean C. Kouam; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
The main objective of this paper is to assess the impact of female unemployment on economic growth in Cameroon. Using the Auto Regressive Distributed Lag (ARDL) model, applied to data covering the period 1987-2020, our results show that the relationship between female unemployment and economic growth in Cameroon is negative and significant in both the short and long runs, which is consistent with Okun's law. This finding reflects the need for the government to support the creation of women's led business and improve the business environment in order to stimulate private investment (private sector support and entrepreneurship promotion). Similarly, labor market institutions should evolve to reduce the rigidity that hinders the willingness and ability of firms to hire women. These measures should actually address the weak capacity of the public sector to create enough jobs to mitigate the severity of women's unemployment.
Keywords: 330; Female Unemployment; Economic growth; NARDL Model